Chiral conversion and periodical decay in bridged-azobenzene photoisomerization: an ab initio on-the-fly nonadiabatic dynamics simulation. Issue 46 (20th April 2016) - Gao, Wanqing; Yu, Le; Zheng, Xiaolei; Lei, Yibo; Zhu, Chaoyuan; Han, Huixian
Abstract : On-the-fly trajectory surface hopping dynamics simulations on the cis ↔ trans photoisomerization mechanisms of bridged-azobenzene upon S1 excitation at the CASSCF level. Abstract : With the implementation of global nonadiabatic switching probability algorithm based on the Zhu–Nakamura theory, we performed on-the-fly trajectory surface hopping simulations at the CASSCF level to analyze the cis ↔ trans photoisomerization mechanism of bridged-azobenzene upon S1 excitation. The cis -to- trans isomerization process was initiated by the pedal-like twist of –NN– moiety and observed hopping to S0 mainly via the cis -form conical intersection region. While, the trans -to- cis process is induced by the nonsymmetrical torsion motion toward the central eight-membered ring and encountered surface hopping through another conical region lying in the middle of the isomerization pathway. In cis -to- trans photoisomerization, we also observed a particular chiral conversion pathway with surface hopping occurs at CI- trans conical region. The trajectories followed this pathway possess relative longer excited state lifetimes as the ∼40 fs initial stage oscillation in the cis Franck–Condon region. Moreover, the periodical population decay pattern of S1 state in trans -to- cis process was observed with an interval of ∼16 fs.